Belize. Significant achievements 2010-2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Belize are identified, during the period from 2010 to 2017, with respect to the needs and interests of the country, strengthening issues such as public policies, food safety and health, biodiversity, gardening, resilience against climate change, animal health, innovation, rural development, good agricultural practices, food and nutritional security. Likewise, technical assistance was provided in the management of post-harvest losses, the use of field schools, the export of cattle, the use of geographic information for risk management and in the fight against antimicrobial resistance. Finally, knowledge transfer was carried out to improve organic production and to benefit the bean, corn, sugar, poultry and ruminant production chains.